2018
DOI: 10.1002/capr.12178
|View full text |Cite
|
Sign up to set email alerts
|

‘Everyone should do it’: Client experience of a 12‐week dialectical behaviour therapy group programme – An interpretative phenomenological analysis

Abstract: Objective There is a dearth of practice‐based evidence of adapted or ‘DBT‐informed’ transdiagnostic models, which could provide services and clinicians with information of what works and for whom, in which settings. This paper aims to bridge this gap by exploring the client experience of a 12‐week transdiagnostic dialectical behaviour therapy (DBT) group programme in a private psychiatric hospital. Method Five participants with varied clinical diagnoses and previous therapeutic experiences were interviewed fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This seems particularly pertinent as local data suggest that 45% of clients are referred to another therapy following 2–6 sessions of CBT. This is also mentioned in the literature; for example, following sessions of CBT, clients are referred to DBT (Childs‐Fegredo & Fellin, ) and to Counselling (Goldman, Brettle, & McAndrew ). Therefore, referring clients as a first line of treatment to therapies other than CBT should be considered, as research demonstrates they are as effective as CBT (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This seems particularly pertinent as local data suggest that 45% of clients are referred to another therapy following 2–6 sessions of CBT. This is also mentioned in the literature; for example, following sessions of CBT, clients are referred to DBT (Childs‐Fegredo & Fellin, ) and to Counselling (Goldman, Brettle, & McAndrew ). Therefore, referring clients as a first line of treatment to therapies other than CBT should be considered, as research demonstrates they are as effective as CBT (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The participants in this study did not appear to adopt a stigmatizing view of themselves or the diagnosis of BPD in part because they and their community adopted a shared language to make sense of problems and because they identified mastery over their problems early on. Even in brief, DBT programmes authors such as Childs‐Fegredo and Fellin (2018) have found that participants found hope in ‘a life worth living’ (a DBT term) and had begun to incorporated DBT skills into their lifestyle. It is possible that talk about successful use and integration of skills into everyday life is predictive of success and recovery in DBT.…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness courses are increasingly being offered in universities (MFS, ). Furthermore, mindfulness practice is a core component of several third‐wave therapies such as dialectical behaviour therapy (DBT; Childs‐Fegredo & Fellin, ), mindfulness‐based stress reduction, MBCT (Segal et al, ), mindful self‐compassion (Neff & Germer, ) and compassion‐focused therapy (CFT; Gilbert, ), which are increasingly accessible to nonclinical populations including university students (Kirby, ; Wilson, Mackintosh, Power, & Chan, ).…”
Section: Conclusion and Implications For Research And Practicementioning
confidence: 99%